2011
DOI: 10.1007/s10815-011-9633-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic testing for the cytogenetic and molecular causes of male infertility: the Mayo Clinic experience

Abstract: Purpose Approximately 8% of couples attempting to conceive are infertile and male infertility accounts for approximately 50% of infertility among couples. Up to 25% of males with non-obstructive infertility have chromosomal abnormalities and/or microdeletions of the long arm of the Ychromosome. These are detected by conventional chromosome and Y-microdeletion analysis. In this study, we reviewed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 27 publications
7
31
0
1
Order By: Relevance
“…Deletions of the different AZF regions occured with different frequency. Confirming previous data [1,15,26], our findings showed that classical AZFc deletions represented the most frequent finding (54.17% of deletions in our cases), followed by the AZFbc region (18.75%), AZFb (10.42%) and AZFa (9.03%). Our data revealed that there was a slightly higher frequency of the AZFa and AZFb microdeletions in infertile patients than previous studies [14,26], which was mainly due to a high rate of partial deletions in AZFa region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Deletions of the different AZF regions occured with different frequency. Confirming previous data [1,15,26], our findings showed that classical AZFc deletions represented the most frequent finding (54.17% of deletions in our cases), followed by the AZFbc region (18.75%), AZFb (10.42%) and AZFa (9.03%). Our data revealed that there was a slightly higher frequency of the AZFa and AZFb microdeletions in infertile patients than previous studies [14,26], which was mainly due to a high rate of partial deletions in AZFa region.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies have reported a wide range (2% to 16%) of chromosomal abnormalities in infertile patients [12,15,30,36]. Reasons for this discrepancy might be ethnic differences or the criteria applied for patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Moreover, the deletion frequency reported in idiopathic AZ and SOZ men (9.09 and 5.5%) in Moroccan population 28 is consistent with our findings in non-Spanish idiopathic AZ and SOZ men (10.7% and 6.9%, respectively). The prevalence of Y microdeletions in our study population (3.3%) is in line with the overall data presented in the literature (3.5%, according to a recent meta-analysis 30 ). When comparing our results with the German population (the lowest ever frequency in the literature 1 ) for similar semen categories, we found slightly higher frequencies in our Spanish population.…”
Section: -124supporting
confidence: 92%
“…The frequency of Y chromosome microdeletions varies between 1% [15] and 55% [16] in the worldwide whereas the few studies performed in Asian male populations showed frequencies of 7.6% to 16.5% in Japan [17][18][19][20][21][22], 11.0% to 19.4% in China [23,24], 10.6% to 11.7% in Taiwan [25,26], 6.4% in Hong Kong [27] and 2.0% to 12.0% in India [12,28,29]. A recently published study reported that the cumulative frequency of Y chromosome microdeletions was 3.5 % in infertile males [30]. It appears that a significant percentage of infertile males with microdeletions in AZF regions do not have children by natural means of reproduction.…”
Section: Abstract Y Chromosome Microdeletion Chromosomal Abnormalitmentioning
confidence: 99%
“…In the general male population, the incidence of chromosomal abnormalities ranges from 0.7% to 1.0%, whereas it is approximately 10.6% among azoospermic and oligozoospermic men [31,32]. The severity of the semen parameters and the frequency of chromosomal abnormalities seem to be positively correlated [30].…”
Section: Abstract Y Chromosome Microdeletion Chromosomal Abnormalitmentioning
confidence: 99%